Sensory analysis of ready-to-eat meals in the Brazilian Army. Issue 4 (4th July 2019) - Carvalho, Mariana Veras; Botelho, Raquel Braz Assunção; De Lacerda, Livia; Zandonadi, Renata Puppin
ABSTRACT: The aim of this study is to evaluate if thermoprocessed meals ready-to-eat (MRE) offered to Brazilian army are nutritious and tasty in comparison to freshly prepared meals (FPM) and to evaluate if the regular consumption of MRE leads to rejection. The nutritional composition and acceptability of FPM and MRE were assessed in a Construction unit, with 92 soldiers. The acceptability assessment took into account length of exposure to the food. Both FPM and MRE presented fat percentages within the recommendation; however, 88% of FPM and 100% of MRE contained more sodium than recommended. Among high-protein meals, MRE presented lower protein and higher moisture than FPM. When introduced, the acceptability of MRE was equal to or greater than FPM. In the long run, acceptability and consumption of MRE decreased significantly. It is recommended that sodium, proteins, and moisture should be adjusted in MRE in order for it to be nutritionally and sensory adequate.